Moralitas Aparatur Sebagai Moderator dalam Upaya Pencegahan Kecurangan Dana Desa - Nawangsari, Nonny Laurencia; Susilowati, Endah (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to examine the influence of internal control systems, apparatus competence, whistleblowing, and good governance on the prevention of village fund fraud, while also assessing the moderating effect of apparatus morality. The study was conducted in Mojowarno District, Jombang Regency, using a quantitative approach. Data were collected from 70 respondents through questionnaires and analyzed using multiple linear regression along with Moderated Regression Analysis (MRA), a statistical method applied to test whether a variable can enhances or reduces the relationship between other variables. The results of the multiple regression analysis indicate that the internal control system has a positive and significant effect on fraud prevention, whereas apparatus competence, whistleblowing, and good governance show no significant impact. The MRA results further reveal that apparatus morality fortify the influence of good governance on fraud prevention but diminishes the relationship between apparatus competence and fraud prevention. Additionally, apparatus morality does not moderate the relationships between whistleblowing or internal control systems and fraud prevention. These findings underscore the vital role of apparatus morality in enhancing governance effectiveness and human resource capacity to prevent fraudulent practices. The study is limited by its narrow geographic scope and exclusive reliance on a quantitative approach. Future research is encouraged to broaden the regional coverage and integrate qualitative methods to gain deeper insights.